2016
DOI: 10.1111/1471-0528.14306
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical lactate as a measure of acidosis and predictor of neonatal risk: a systematic review

Abstract: Background Umbilical cord lactate is one approach to measuring acidosis and intrapartum hypoxia, knowledge of which may be helpful for clinicians involved in the care of women and newborns.Objective To synthesise the evidence on accuracy of umbilical cord lactate in measuring acidosis and predicting poor neonatal outcome.Search strategy Studies published and unpublished between 1990 and 2014 from PubMed/Medline, EMBASE, Cochrane Central Register of Controlled Trials, and clinicaltrials.gov were assessed.Select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 72 publications
1
40
0
4
Order By: Relevance
“…As base deficit reflects the patient's total metabolic and circulatory status , the observed improvement might indicate that most patients' requirements were met during transport. This is reassuring given both the composition of the highly vulnerable study population and the fact that the median stabilisation time was significantly shorter than previously reported .…”
Section: Discussionsupporting
confidence: 69%
“…As base deficit reflects the patient's total metabolic and circulatory status , the observed improvement might indicate that most patients' requirements were met during transport. This is reassuring given both the composition of the highly vulnerable study population and the fact that the median stabilisation time was significantly shorter than previously reported .…”
Section: Discussionsupporting
confidence: 69%
“…We performed a randomized clinical trial to test the hypothesis that room air for category II fetal heart tracings is noninferior to oxygen in improving fetal metabolic status as represented by umbilical artery lactate, a marker of metabolic acidosis and neonatal morbidity. [17][18][19]…”
mentioning
confidence: 99%
“…In addition, the use of antiretroviral therapy (ART) in pregnancy might affect the measurement of acidosis. A previous study found that umbilical artery lactate is an inexpensive and effective way to measure acidosis in the clinic and can be used in the assessment of neonatal outcome. Consequently, the aim of the present prospective cohort study was to assess umbilical artery lactate results (as a measure of acidosis) and intrapartum and neonatal outcomes among women with and without HIV who were delivering in a large tertiary unit in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, the use of antiretroviral therapy (ART) in pregnancy might affect the measurement of acidosis. A previous study 8 found that umbilical artery lactate is an inexpensive and effective way to measure acidosis in the clinic and can be used in the assessment of neonatal outcome.…”
mentioning
confidence: 99%